PhD programs in Africa: The Arrows, the Targets, and the Archers - (:unkn) unknown (My University, 2022)
The research ecosystem in sub-Saharan Africa is changing. Organised around new centres of scientific excellence, the sub-continent is building a research agenda aimed toward major development challenges and the achievement of the sustainable development goals. Thus, strengthening doctoral programs and their beneficiaries becomes crucial in supporting this transformation. However, great challenges remain in the designing and implementation of impactful scholarship programs to accompany the creation of African scientific communities of excellence. Stakeholders suffer from a lack of investment in research infrastructure and its operators as well as the absence of sufficient qualified supervisory staff. An increase in the student population and heavy dependence on international partnerships accentuates these challenges. In this context, five doctoral support programs operators in sub-Saharan Africa (ICIPE, IRD, LPI and UNU) offer an inventory of the challenges associated with regional doctoral support. We offer a field vision, based on experience supporting over 1,500 doctoral students in SubSaharan Africa. We propose an approach that addresses SDG 4 - Quality Education and 9 - Industry, Innovation and Infrastructures (mainly objectives 4.b and 9.5) and demonstrate how these programs have become vectors in building sustainable solutions to development challenges in Africa. This proposal aims to draw up the archetype of an impactful regional doctoral program in SubSaharan African that also ensures the well-being of the students involved. This contribution is intended for decision-makers (public and private) and national and international donors committed to strengthening research funding in sub-Saharan Africa through doctoral programs.
Keywords: African Research